Programa de Atividade Física Adaptada com Uso de Vídeo Game: o que Pensam os Alunos? - Silva, Fernanda Carolina Toledo da [UNESP]; Braccialli, Lígia Maria Presumido [UNESP] (My University, 2014)
Exergames are a new educational tool, and have been used by teachers in physical education classes because it is an activity that provides entertainment and caloric expenditure. The goal of this study was to verify the opinion of students in an elementary school class on a program of adapted physical activity using the videogame, developed during physical education classes. Study participants were students in a fourth-grade elementary school class that had a student with disability. The researcher and the Physical Education teacher elaborated the planning program of an adapted physical activity with the use of videogames. The classes were recorded in a log book and group interviews were conducted at the end of each class. The results showed that the classes were nice, fun and interesting experiences. The study concluded that the program was successful.

Os exergames são uma nova ferramenta educacional, e têm sido utilizados pelos professores nas aulas de Educação Física por se tratar de atividade que proporciona gasto calórico e entretenimento. O objetivo do estudo foi verificar a opinião dos alunos de uma turma de ensino fundamental sobre um programa de atividade física adaptada com o uso do videogame, desenvolvido durante as aulas de Educação Física. Participaram do estudo alunos de uma turma do quarto ano do Ensino Fundamental I que tinha um aluno com deficiência física matriculado. O pesquisador e pelo professor de Educação Física da turma, elaboraram o planejamento de um programa de atividade física adaptada com o uso de videogame. As aulas realizadas foram registradas em diário de campo e ao final de cada aula foram realizadas entrevistas coletivas. Os resultados apontaram que as aulas foram experiências legais, divertidas e interessantes. Conclui-se que o programa foi realizado com sucesso.
Adapted physical activity progra using video games: what do students think?
Keywords: video games; paralisia cerebral; educação especial; educação física